The impact of the environment on health in Mongolia: A systematic review - Jadambaa, A.; Spickett, Jeffery; Badrakh, B.; Norman, R. (SAGE Publications Inc., 2015)
Mongolia has significant exposure to environmental risk factors because of poor environmental management and behaviors, and children are increasingly vulnerable to these threats. This study aimed to assess levels of exposure and summarize the evidence for associations between exposures to environmental risk factors and adverse health outcomes in Mongolia, with a particular focus on children. A systematic review was conducted using the PubMed, EMBASE, Web of Science, Global Health Library, CINAHL, CABI, Scopus, and mongolmed.mn electronic databases up to April 2014. A total of 59 studies meeting the predetermined criteria were included. Results indicate that the Mongolian population has significant exposure to outdoor and indoor air pollution, metals, environmental tobacco smoke, and other chemical toxins, and these risk factors have been linked to respiratory and cardiovascular diseases among adults and respiratory diseases and neurodevelopmental disorders among children. Well-designed epidemiological investigations in vulnerable populations especially in pregnant women and children are recommended.